2015
DOI: 10.1016/j.redox.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of nitric oxide in the regulation of tumor cell response and resistance to photodynamic therapy

Abstract: Photodynamic therapy (PDT) against cancer has gained attention due to the successful outcome in some cancers, particularly those on the skin. However, there have been limitations to PDT applications in deep cancers and, occasionally, PDT treatment resulted in tumor recurrence. A better understanding of the underlying molecular mechanisms of PDT-induced cytotoxicity and cytoprotection should facilitate the development of better approaches to inhibit the cytoprotective effects and also augment PDT-mediated cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 90 publications
5
42
0
1
Order By: Relevance
“…Importantly, apoptosis induction by photodynamic therapy was inhibited in their experiments when the activity of NOS was blocked (54,55). Therefore, it is obvious that under the conditions of the test system described by Rapozzi et al, the concentration of singlet oxygen was not sufficiently high to cause direct apoptosis induction.…”
Section: Figure 3 Inactivation Of Catalase By Low Concentrations Of mentioning
confidence: 96%
See 2 more Smart Citations
“…Importantly, apoptosis induction by photodynamic therapy was inhibited in their experiments when the activity of NOS was blocked (54,55). Therefore, it is obvious that under the conditions of the test system described by Rapozzi et al, the concentration of singlet oxygen was not sufficiently high to cause direct apoptosis induction.…”
Section: Figure 3 Inactivation Of Catalase By Low Concentrations Of mentioning
confidence: 96%
“…It is, therefore, attractive to speculate that induction of NOS by photodynamic therapy might have caused a sufficiently high concentration of NO for the transient inhibition of membrane-associated catalase, in analogy to the induction by the FAS system (6) or by interferons (52). As a result, the generation of secondary singlet oxygen, FAS receptor involvement, catalase inactivation and reactivation of intercellular ROS/RNS signalling might have been the dominant cause of apoptosis induction, in addition to the other effects of NO characterized by Rapozzi et al (54), Thus the selective uptake of the photosensitizer might have led to NO-mediated catalase inhibition, followed by selective inactivation of catalase by secondary singlet oxygen and subsequent ROS/RNS-dependent apoptosis-inducing signaling.…”
Section: Figure 3 Inactivation Of Catalase By Low Concentrations Of mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Rapozzi et al [70,71,72] reported that endogenous iNOS/NO can modulate pheophorbide a-sensitized photokilling of melanoma cells in distinct ways, depending on the intensity of photodynamic action. Thus, low level NO induced by modest photooxidative pressure signaled for cytoprotection via upregulation of anti-apoptotic NF-κB and Snail (zinc finger protein SNAI1), but down-regulation of RKIP (Raf kinase inhibitor protein).…”
Section: Duality Of Inos/no-mediated Signaling In Pdtmentioning
confidence: 99%
“…Thus, low level NO induced by modest photooxidative pressure signaled for cytoprotection via upregulation of anti-apoptotic NF-κB and Snail (zinc finger protein SNAI1), but down-regulation of RKIP (Raf kinase inhibitor protein). In contrast, a higher level of NO induced by greater photooxidative pressure signaled for less protection (greater apoptosis) via down-regulation of NF-κB and Snail, but upregulation of RKIP [70,71,72]. Therefore, a pro- vs. anti-PDT signaling role for endogenous NO was demonstrated based on the level of photodynamic pressure applied.…”
Section: Duality Of Inos/no-mediated Signaling In Pdtmentioning
confidence: 99%